Desempenho bioeconômico de genótipos bovinos terminados em sistema intensivo de pastagem no meio-norte do Brasil - Lima Neto, Anisio Ferreira (2018)
The Brazilian beef cattle ranching is characterized by productive systems adjusted to the different biomes and socio-cultural patterns of each region. The objective of the present study was to assess the bio-economic performance of beef cattle in the Mid- North Region of Brazil, finished in an intensive pasture system with the use of irrigation. We attempted to assess the performance of different genotypes created in the breeding and rearing phase in extensive systems, evaluating the productive performance when finished in an irrigated pasture system, fertilized and intensively managed, assessing individual weight gain, weight per area, stocking rate, followed by economic analysis of the system when composed of Nellore, Crusaders and “Curraleiro Pé-Duro” genotypes, in the coastal table-lands of the state of Piauí. The experimental design adopted was randomized blocks, where pickets were used as blocks and the animals as a repetition, the genetic grouping being the treatments assessed. Forage consumption was evaluated based on the difference in forage weight in pre and post grazing, obtaining the fodder consumed by the animals. The samples to stop this calculation were carried out in number of five per picket at the time of entry and exit of the lot, 615 kg of nitrogen was used per hectare year as fertilizer of production, irrigation was applied to every two days and with a 7mm blade per day, and the animals were weighed individually every 50 days. For the economic analysis, we obtained the purchase balances, inventory of investments, to calculate the effective operating cost, total operating cost, gross margin, net margin and profitability, being the simulated calculations for the total area of the central pivot, considering the area individually composed by each genetic group and based on the performance of the genocide the economic analysis was carried out. The performance of the evaluated genotypes were grouped in periods of the weightings, totalizing three weightings, with interval of 50 days each, counted from the date of entry of the animals in the pasture. The average gains of daily weight found for the animals Nellore, Crusader and “Curraleiro Pé-Duro” were 0.782 g / day, 0.851 g / day and 0.531 g / day, the gain per area was 87.75 kg / ha / month, 95.6 kg / ha / month and 59, (P˂0.05) by the genetic group, where the Nellore and Crusader animals obtained a higher weight gain than the animals Curraleiro Pé-Duro in the period termination time of 150 days. The nutritional value of Megathyrsus maximus cv. Mombasa was 16.2% CP, 59.77% NDT, FDA 31.29 and NDF 54.97, forage supply did not vary significantly within the experimental period, maintaining an average of 4.27 kgMS / 100 kg of PV, the stocking rate of 6.20 AU / hectare,% CMS based on live weight ranged from 3.6 to 2.69%, the consumption of PB (kg) and NDT (kg) in the three weighing periods were consumption requirements to achieve gains of 0.536 g / day, 1.113 kg / day and 0.690 kg / day respectively at 50,100 and 150 days of termination, these values compared to the NRC (2017) and BR-Corte (2016) the values obtained were lower than those found in the experiment. The results obtained per monthly effective operational cost @ was R $ 143.17, R $ 97.28 and R $ 83.28 / month / @ for the genetic group CPD, Nellore and Crusader respectively, the gross margin / @ was R $ 8.83, R $ 54.72 and R $ 68.73 for the CPD, Nellore and Cruzado groups, respectively, net margin / @ was R $ -24.81, R $ 31.86 and R $ 47.75 for the CPD group, Nellore and Crusader, profit / @ was -24.8%, 20.9% and 31.41% for the CPD, Nellore and Crusades group. The use of nitrogen can be reduced by half in the assessed system guaranteeing the fulfillment of the nutritional requirements of the animals. Curraleiro Pé-Duro animals are not recommended for systems that recommend high use of inputs, and Nellore and Crusaders express better gains.